1980
DOI: 10.1142/s0192415x80000141
|View full text |Cite
|
Sign up to set email alerts
|

The Acupunture Treatment of Low Back Pain: A Randomized Controlled Study

Abstract: The acupuncture treatment situation was beneficial to the majority of people with low back pain. This was shown by the use of short-term controls and long-term controls, although the latter were not intended in the study design. After acupuncture, there was a 51% pain reduction in the average pain score in the Immediate Treatment Group. The short-term controls, the Delayed Treatment Group, had no reduction whatsoever in their pain scores at the comparable followup period. Later, the Delayed Treatment Group ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
12

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 0 publications
2
53
0
12
Order By: Relevance
“…The proportion of "disc lesions" that had electromyographic study in corroboration of the clinical findings was only presented in four reports (Leung, 1973;Gunn et al, 1980;Maruyama, 1984;Liu Xi-Min et al, 1984: see Table 4). The majority of studies did use X-ray films, with only three of these reporting results in all cases (Leung, 1979;Coan et al, 1980;Gunn et al, 1980) and several others reporting results only as a part of their single-case studies (Wang Qing and Wang Fuchun, 1986;Arseni et al, 1989;Liu Wendou, 1990;Wang Wenliang et al, 1991). This problem was further compounded by the lack of reported clinical information/ tests in some studies.…”
Section: Shortcomings In Research Methodology In Ap Studies Of Nonopementioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of "disc lesions" that had electromyographic study in corroboration of the clinical findings was only presented in four reports (Leung, 1973;Gunn et al, 1980;Maruyama, 1984;Liu Xi-Min et al, 1984: see Table 4). The majority of studies did use X-ray films, with only three of these reporting results in all cases (Leung, 1979;Coan et al, 1980;Gunn et al, 1980) and several others reporting results only as a part of their single-case studies (Wang Qing and Wang Fuchun, 1986;Arseni et al, 1989;Liu Wendou, 1990;Wang Wenliang et al, 1991). This problem was further compounded by the lack of reported clinical information/ tests in some studies.…”
Section: Shortcomings In Research Methodology In Ap Studies Of Nonopementioning
confidence: 99%
“…In other studies, primarily those from China, it was stated in virtually all the reports that SLR was part of the assessment, but no details were given regarding individual angles except in some single cases (Coan et al, 1980;Maruyama, 1984;Jiang Youguang et al, 1984;Gao Wenjie, 1988;Bi Fugao, 1990;Li Fengbo, 1990;Liu Wendou, 1990;Wang Wenliang et al, 1991;Longworth, 1991;Xin Bochen, 1991). One study reported that just 25% of cases had a positive SLR (Dou Kechen, 1991).…”
Section: Shortcomings In Research Methodology In Ap Studies Of Nonopementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in a pragmatic trial, where trial acupuncturists could treat patients in the same manner they would in routine practice, the acupuncturists did not express such constrains-with the exception of two practitioners, who found the number of treatments allowed in the trial treatments to be insufficient [76]. In fact, one study changed its design from sham acupuncture controlled to active treatment controlled trial because the trial acupuncturists considered it unethical to provide the sham treatment [77].…”
Section: Studies Of Participants In Clinical Trialsmentioning
confidence: 99%
“…A number of trials of acupuncture have been conducted claiming that they were testing classic or traditional acupuncture often without description of the actual interventions used and with no citation of any relevant texts (Coan et al, 1980) to substantiate the claim that the treatments they applied were related to a particular tradition (Birch, 1997c). Acupuncture is a diverse medical system with many styles and methods used (Birch, 1998;Birch and Felt, 1999;MacPherson and Kaptchuk, 1997), even within the same tradition of practice (Birch and Sherman, 1999).…”
Section: Steps Taken To Validate the Traditionally Based System Of Acmentioning
confidence: 99%